(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Rice productivity influences by different agronomic factors among which planting geometry and nitrogen fertilization are important for obtaining higher yield by proper utilizing the growth elements and enhancing soil aeration to create congenial field condition. Therefore, this study was designed to define suitable planting geometry and nitrogen management for getting higher yield in Boro rice. The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh, during the period from December 2017 to May 2018 to study the effect of planting geometry and time of nitrogen application on the yield of Boro rice cv. BRRI dhan45. The experimental treatments comprised four spacings viz. 20 cm × 10 cm, 20 cm × 15 cm, 20 cm × 20 cm and 25 cm × 15 cm and four times of nitrogen (138kg N ha-1) application namely, nitrogen applied in two equal splits at (i) 15 and 45 days after transplanting (DAT) (ii) 20 and 40 DAT, and in three equal splits at (iii) 0, 20 and 40 DAT and (iv) 20, 40 and 60 DAT. The experiment was conducted in a split plot design with three replications assigning time of nitrogen application in the main plot and spacing in the sub-plot. Spacing showed significant effect on all the yield contributing characters except weight of 1000 grains and yield. The results revealed that the highest grain yield (5.46 t ha-1) was obtained from 20 cm × 15 cm spacing, while the lowest one (4.66 t ha-1) was obtained from 20 cm × 10 cm spacing. All the yield contributing characters were significantly influenced by time of nitrogen application except weight of 1000 grains. The highest grain yield (5.48 t ha-1) was obtained from application of nitrogen in three equal splits at 20, 40 and 60 DAT, while the lowest one (4.60 t ha-1) was obtained from nitrogen application in two equal splits at 20 and 40 DAT. Interaction between spacing and time of nitrogen application significantly influenced all the parameters except panicle length, weight of 1000 grains and biological yield. The highest grain yield (5.85 t ha-1) was obtained from 20 cm × 15 cm spacing with application of nitrogen in three equal splits at 20, 40 and 60 DAT. Therefore, BRRI dhan45 can be transplanted at 20 cm × 15 cm spacing along with application of nitrogen in three equal splits at 20, 40 and 60 DAT for higher grain yield. J Bangladesh Agril Univ 18(3): 599–605, 2020 https://doi.org/10.5455/JBAU.114116